Enhancement in the thermomechanical properties of carbon fibre–carbon nanotubes–epoxy hybrid composites. (8th October 2012) - Mathur, R.B.; Singh, B.P.; Tiwari, Pankaj K.; Gupta, T.K.; Choudhary, Veena
Multiwalled carbon nanotubes (MWCNTs) were grown on carbon fibre (CF) cloth substrates by chemical vapour deposition (CVD) that resulted in strong anchoring of these tubes on the CF surface. These hybrid preforms were used as the reinforcement in epoxy resin matrix to develop hybrid or multiscale CF–MWCNT/epoxy composites (CF–MWCNT/epoxy). The flexural strength (FS) as well as the flexural modulus (FM) of these composites was found to increase with increasing amount of CNTs grown on CF surface. FS of the hybrid composites improved by 80%, i.e., 560 MPa when compared with 310 MPa for the base composite (CF/epoxy) prepared under identical conditions. FM of these composites also improved by 120%, i.e., 55 GPa for the hybrid composite when compared with 25 GPa for the base composite. The in–plane and the transverse thermal conductivity of these hybrid composites improved from 17.68 W/mK and 1.79 W/mK, respectively, for base composite to 29.05 W/mK to 2.61 W/mK for the hybrid composite.